x 4 − 1 6 x 3 + 8 9 x 2 − 2 0 6 x + 1 6 8 = 0
What will be the sum of all the values of x satisfying the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The equation is
x 4 − 2 x 3 − 1 4 x 3 + 2 8 x 2 + 6 1 x 2 − 1 2 2 x − 8 4 x + 1 6 8 = 0
⇒ x 3 ( x − 2 ) − 1 4 x 2 ( x − 2 ) + 6 1 x ( x − 2 ) − 8 4 ( x − 2 )
Implies that, ( x − 2 ) ( x 3 − 3 x 2 − 1 1 x 2 + 3 3 x + 2 8 x − 8 4 ) = 0
So, ( x − 2 ) ( x 2 ( x − 3 ) − 1 1 x ( x − 3 ) + 2 8 ( x − 3 ) ) = 0
( x − 2 ) ( x − 3 ) ( x 2 − 1 1 x + 2 8 ) = 0
⇒ ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 7 ) = 0
So, the zeroes are: 2 , 3 , 4 , 7 and the sum is 1 6
Problem Loading...
Note Loading...
Set Loading...
Vieta's Formula explains it all...
Considering the coefficients of the equation, if a = 1 and b = − 1 6 , then − a b = 1 6 . Thus, the sum of all roots is 1 6 aka x 1 + x 2 + x 3 + x 4 = 1 6 where x 1 , x 2 , x 3 , x 4 are solutions to the quartic equation.